2010
DOI: 10.1007/s10532-010-9426-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of pharmaceutically active compounds by a ligninolytic fungal peroxidase

Abstract: Pharmaceuticals are an important group of emerging pollutants with increasing interest due to their rising consumption and the evidence for ecotoxicological effects associated to trace amounts in aquatic environments. In this paper, we assessed the potential degradation of a series of pharmaceuticals: antibiotics (sulfamethoxazole), antidepressives (citalopram hydrobromide and fluoxetine hydrochloride), antiepileptics (carbamazepine), anti-inflammatory drugs (diclofenac and naproxen) and estrogen hormones (est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…The results demonstrated that 64 to 80 % of the initial SMX (2.5 mg/L) was degraded after 7 h. In addition, experiments conducted at a higher SMX concentration (25 mg/L) resulted in the detection of a metabolite identified and confirmed using an authentic standard as 3-amino-5-methylisoxazole (Eibes et al 2011).…”
Section: Success Of Individual Microorganismsmentioning
confidence: 83%
“…The results demonstrated that 64 to 80 % of the initial SMX (2.5 mg/L) was degraded after 7 h. In addition, experiments conducted at a higher SMX concentration (25 mg/L) resulted in the detection of a metabolite identified and confirmed using an authentic standard as 3-amino-5-methylisoxazole (Eibes et al 2011).…”
Section: Success Of Individual Microorganismsmentioning
confidence: 83%
“…[21][22][23]. Also a versatile peroxidase from the ligninolytic fungus Bjerkandera adusta showed SMX breakdown activity [32]. The accumulation of 3A5MI, resultant of aerobic SMX degradation, seems to be common, being observed also in Microbacterium sp.…”
Section: Discussionmentioning
confidence: 96%
“…The accumulation of 3A5MI, resultant of aerobic SMX degradation, seems to be common, being observed also in Microbacterium sp. BR1 [28], activated sludge [18] or produced by the above mentioned per-oxidase [32]. Nevertheless, different reaction mechanisms may be involved on SMX breakdown with accumulation of this metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Phenothiazenes, for example, have been used to initiate the polymerization of sterically demanding phenols, [32,33] or ABTS to facilitate pyrrole polymerization [34,35]. Also transition metals (e.g., Mn 2+/3+ ) [36] or polyoxometallates [37] have been reported. Second, the mediator radical itself can initiate chain growth thereby being incorporated into the polymer (see Section 2.4).…”
Section: Laccase-/peroxidase-mediator-systems (Lms/pms)mentioning
confidence: 99%
“…Likewise halophenols [178][179][180][181][182] bisphenol A, [183][184][185] various hormones and so-called endocrine disrupting compounds [186][187][188] or even TNT [189,190] have been reported. Non-phenolic compounds may be ‗inactivated' using the LMS or PMS strategy [36,[191][192][193][194][195][196][197][198].…”
Section: Phenol Detoxificationmentioning
confidence: 99%